2022
DOI: 10.3389/fcell.2021.780749
|View full text |Cite
|
Sign up to set email alerts
|

Notochordal Cell-Based Treatment Strategies and Their Potential in Intervertebral Disc Regeneration

Abstract: Chronic low back pain is the number one cause of years lived with disability. In about 40% of patients, chronic lower back pain is related to intervertebral disc (IVD) degeneration. The standard-of-care focuses on symptomatic relief, while surgery is the last resort. Emerging therapeutic strategies target the underlying cause of IVD degeneration and increasingly focus on the relatively overlooked notochordal cells (NCs). NCs are derived from the notochord and once the notochord regresses they remain in the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 201 publications
0
39
0
Order By: Relevance
“…Our results suggest that expansion in hyperosmolar conditions could direct the degenerated NPCs to a more progenitor‐like and healthy phenotype. While there is no consensus on a set of phenotypic markers that can identify healthy NPCs, we focused on ACAN, PAX1, and CD24 expression as known markers of a healthy human IVD recently reviewed by Bach et al 42 Gene and protein levels of these NPC markers were increased following expansion in 500 mOsm/L. Given that high levels of CD24 are seen in the fetal NP, 51 this suggests that hyperosmolar conditions result in NPCs with a young and healthy phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggest that expansion in hyperosmolar conditions could direct the degenerated NPCs to a more progenitor‐like and healthy phenotype. While there is no consensus on a set of phenotypic markers that can identify healthy NPCs, we focused on ACAN, PAX1, and CD24 expression as known markers of a healthy human IVD recently reviewed by Bach et al 42 Gene and protein levels of these NPC markers were increased following expansion in 500 mOsm/L. Given that high levels of CD24 are seen in the fetal NP, 51 this suggests that hyperosmolar conditions result in NPCs with a young and healthy phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Complete dog spines were collected from Beagles euthanized in unrelated ethically approved research studies (Table 1). Beagles are chondrodystrophic dogs in which notochordal cells (NCs) are lost and replaced by NPCs between 3 and 12 months of age comparable to humans in which we also see a complete loss of NCs before adulthood has reached 42 . As the role of sex in IVD degeneration has not been consistently studied to date, NPCs of an equal amount of male and female donors were included in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disappearance of NCs often marks the onset of early IDD, so people are always interested in the underlying mechanisms by which NCs maintain the healthy state of IVD and see the above mechanisms as hope for IVD regeneration. To date, therapeutic NCs have been found to promote matrix production of NPCs, increase cell proliferation, reduce apoptosis, and inhibit angiogenesis and neurogenesis ( Bach et al, 2021 ). A recently study has also confirmed the therapeutic effect of NCs-derived exosomes.…”
Section: Application Of Exosomes and Exosomal Mirnas In Intervertebra...mentioning
confidence: 99%
“…The loss of the adult nucleus pulposus (NP) cells is considered one of the main factors of IDD, which lead to the reduction of glycosaminoglycan and collagen II, and affect the function of human IVDs [ 3 , 4 ]. A promising strategy to improve the function of the damaged intervertebral disc (IVD) is to induce de novo regeneration of NP tissue through the integration of transplanted stem cells [ 5 ]. However, most studies have predominantly conducted transplantation of either mesenchymal stem cells (MSCs) [ 6 ] or pluripotent stem cells (PSCs) [ 7 ], both of which exhibit unsatisfactory IDD regeneration performance in hypoxia, acidulous and inflammatory IDD microenvironment [ 8 ].…”
Section: Introductionmentioning
confidence: 99%